1985
DOI: 10.1126/science.228.4700.731
|View full text |Cite
|
Sign up to set email alerts
|

Recurring Origins of Allopolyploid Species in Asplenium

Abstract: A large proportion of plant species has originated through allopolyploidy: interspecific hybridization followed by chromosome doubling. Heterozygosity remains fixed in allopolyploids because of nonsegregation of parental chromosomes. Two allotetraploid species of the fern genus Asplenium show allozyme polymorphisms at loci that are polymorphic in their diploid progenitors, indicating that each has originated more than once and implicating continued gene flow from diploids to tetraploids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
1

Year Published

1986
1986
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(73 citation statements)
references
References 15 publications
2
69
0
1
Order By: Relevance
“…Many examples of variation in locus copy number among tetraploid populations can also be found in the plant literature [35][36][37] . Asplenium bradleyi is a tetraploid fern formed by the hybridization of A. platyneuron and A. montanum, which are both diploid 36 .…”
Section: 'Lynch and Conerymentioning
confidence: 99%
See 1 more Smart Citation
“…Many examples of variation in locus copy number among tetraploid populations can also be found in the plant literature [35][36][37] . Asplenium bradleyi is a tetraploid fern formed by the hybridization of A. platyneuron and A. montanum, which are both diploid 36 .…”
Section: 'Lynch and Conerymentioning
confidence: 99%
“…Asplenium bradleyi is a tetraploid fern formed by the hybridization of A. platyneuron and A. montanum, which are both diploid 36 . Comparisons of isozyme expression patterns in these species showed that one of the A. bradleyi populations had lost the isocitrate dehydrogenase (IDH) locus that came from A. montanum 36 Comparisons between tetraploid taxa and their diploid sister groups can determine if the association between genome duplication and speciation that we see in Paracanthopterygii (the group that includes salmonids and osmerids) is widespread. Some 50-70% of angiosperms appear to have experienced genome doubling 39 , therefore it might be especially prudent to survey this group for a phylogenetic link between polyploidy and speciation.…”
Section: 'Lynch and Conerymentioning
confidence: 99%
“…This mode of origin for allopolyploids has been documented previously for the angiosperms Tragopogon mirus and T. miscellus (Roose & Gottlieb, 1976;, the ptendophytes Asplenium bradleyi D. C. Eaton and A. pinnatifidium Nutt. (Werth et a!., 1985) and the bryo- , 1988). There is also recent evidence that autopolyploids of the angiosperm Heuchera micrantha Dougi.…”
mentioning
confidence: 99%
“…Multiple origins of allopolyploids have, on rare occasions, been suggested, based on allozyme data (Roose and Gottlieb, 1976;Werth et al, 1985;Wyatt et al, 1988). The fact that autotetraploids in H. micrantha are not only numerous and widespread but are also of multiple origin is significant because, unlike allopolyploidy, autopolyploidy typically has been considered to be rare and of little evolutionary importance (Stebbins, 1950;Lewis, 1980;Levin, 1983;Soltis and Rieseberg, 1986).…”
Section: Discussionmentioning
confidence: 99%